2021
DOI: 10.1002/eap.2328
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of space use by free‐ranging domestic dogs Canis familiaris in rural Africa

Abstract: Variation in the spatial ecology of animals influences the transmission of infections and so understanding host behavior can improve the control of diseases. Despite the global distribution of free-ranging domestic dogs Canis familiaris and their role as reservoirs for zoonotic diseases, little is known about the dynamics of their space use. We deployed GPS loggers on owned but free-ranging dogs from six villages in rural Chad, and tracked the movements of 174 individuals in the dry season and 151 in the wet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Animals in our study were only monitored during the dry and hot season, but seasonal weather changes could also be a factor affecting HR size. Dürr et al (2017) and Wilson‐Aggarwal, Goodwin, Moundai, et al (2021) found in their respective studies in Australia and Chad that FRDD roamed less during the wet season. Tracking dogs in Blantyre city during the wet season would be necessary to identify whether these seasonal differences that could be relevant for disease transmission exist.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Animals in our study were only monitored during the dry and hot season, but seasonal weather changes could also be a factor affecting HR size. Dürr et al (2017) and Wilson‐Aggarwal, Goodwin, Moundai, et al (2021) found in their respective studies in Australia and Chad that FRDD roamed less during the wet season. Tracking dogs in Blantyre city during the wet season would be necessary to identify whether these seasonal differences that could be relevant for disease transmission exist.…”
Section: Discussionmentioning
confidence: 98%
“…The association between HR95 size and the number of adults and children in the household might suggest differences in interactions affecting dog roaming behavior. Previous studies showed that dog movements are affected by the activities of their owners (Hudson et al, 2017; Maher et al, 2019; Wilson‐Aggarwal, Goodwin, Moundai, et al, 2021). For example, in urban Malawi, children commonly take care of the dogs and are often accompanied by them when they walk or play away from the household.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high relevance of accurate HR estimates for diverse questions in ecology and conservations [ 58 , 83 ], adding this predictive power can facilitate ecological application and improve the prediction accuracy of future models. For instance, HR overlap among neighbors is often important for disease and parasite transmission [ 84 , 85 ]. Future studies can also further explore possible effects of population density (that had no effect in this system) and HR overlap on behavioral movement indices of individuals and their predictability.…”
Section: Discussionmentioning
confidence: 99%
“…The median percentage of GPS fixes of dogs near ponds was 0.25% (Inter-quartile range = 0%-2.96%), 0.23% (0%-0.87%) and 0.26% (0%-3.11%) in the hot-dry, wet and cool-dry seasons, respectively. Additional detail of the spatial behaviors of these dogs is provided by Wilson-Aggarwal et al 29…”
Section: Dog Movement Ecologymentioning
confidence: 99%
“…12 In this study, we investigate the ecology and epidemiology of Guinea worm in domestic dogs living along the River Chari, Chad (Figure 1), because these now constitute the major host of what was thought to be an exclusively human parasite. We studied cohorts of dogs over three climatic seasons, tracked their space use with GPS loggers, 29 and used stable isotope analysis 30 of dog whiskers in a forensic reconstruction of their diets. 31 We use these data in a retrospective analysis to test hypotheses linking the ecology of individual dogs, primarily their diets and consumption of fish, with variation in their prior histories of Guinea worm disease.…”
Section: Introductionmentioning
confidence: 99%